Isolation and Characterisation of Alongshan Virus in Russia - Kholodilov, Ivan S.; Litov, Alexander G.; Klimentov, Alexander S.; Belova, Oxana A.; Polienko, Alexandra E.; Nikitin, Nikolai A.; Shchetinin, Alexey M.; Ivannikova, Anna Y.; Bell-Sakyi, Lesley; Yakovlev, Alexander S.; Bugmyrin, Sergey V.; Bespyatova, Liubov A.; et al. (Viruses, 2020)
In recent decades, many new flavi-like viruses have been discovered predominantly in different invertebrates and, as was recently shown, some of them may cause disease in humans. The Jingmenvirus (JMV) group holds a special place among flaviviruses and flavi-like viruses because they have a segmented ssRNA(+) genome. We detected Alongshan virus (ALSV), which is a representative of the JMV group, in ten pools of adult Ixodes persulcatus ticks collected in two geographically-separated Russian regions. Three of the ten strains were isolated in the tick cell line IRE/CTVM19. One of the strains persisted in the IRE/CTVM19 cells without cytopathic effect for three years. Most ALSV virions purified from tick cells were spherical with a diameter of approximately 40.5 nm. In addition, we found smaller particles of approximately 13.1 nm in diameter. We obtained full genome sequences of all four segments of two of the isolated ALSV strains, and partial sequences of one segment from the third strain. Phylogenetic analysis on genome segment 2 of the JMV group clustered our novel strains with other ALSV strains. We found evidence for the existence of a novel upstream open reading frame in the glycoprotein-coding segment of ALSV and other members of the JMV group.